Health Promotion Media and Their Influence on Behavioral Change: A Literature Review on The Role of Social Media in Health Promotion - Yudha Pamungkas Pratama; Andi Hariati; Andi Asrina; Yusriani Yusriani; Fairus Prihatin (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This systematic review examined how social media-based health-promotion interventions are associated with health-related behavioral outcomes across diverse populations and contexts. Research Method: Following PRISMA 2020, Scopus, PubMed, Web of Science, and ScienceDirect were searched for eligible studies published from January 2020 to May 2026. Forty studies met the inclusion criteria. Risk of bias and methodological quality were evaluated using RoB 2 and appropriate JBI critical appraisal checklists, and findings were synthesized narratively by outcome category. Results and Discussion: The evidence indicated favorable associations with health literacy, vaccination-related outcomes, physical activity, dietary practices, smoking cessation, mental health awareness, and preventive practices. Interactive communication, peer support, online communities, credible influencers, and tailored messages supported engagement. However, heterogeneous designs and measures prevented causal conclusions, while misinformation, privacy risks, digital inequality, and limited long-term evidence constrained interpretation. Implications: Health organizations should combine audience-appropriate content with professional oversight, privacy safeguards, misinformation management, and inclusive access. Longitudinal and experimental studies using validated behavioral measures are needed. Originality: This review distinguishes engagement, knowledge, and intention from self-reported, objectively measured, and sustained behavioral change.